Wear resistance and tribological properties of high entropy coatings CrNiTiZrCu - Eremin, E.N.; Yurov, V.M.; Guchenko, S.A. (Eurasian Physical Technical Journal, 2020)
A highly entropic alloy was first synthesized in the work by mechanical alloying followed by heat treatment in vacuum under certain conditions. The microhardness of the CrNiTiZrCu coating is not inferior and in most cases exceeds the hardness of highly entropic equiatomic alloys. The wear resistance of the CrNiTiZrCu coating is 3•10-4 g/min, which also meets the special steels for wear resistance. High entropy coating has a low coefficient of friction (0.04) at the level of friction of layered crystals, which distinguishes them from high-entropy alloys (about 0.4-0.6) by an order of magnitude. They turn out to be anti-friction, which in all probability leads to energy savings. The coating is already used in the manufacture of turbine blades made of steel 20X13 at a turbo-mechanical plant in Karaganda.
Keywords: highly entropic coatings; target; equiatomic proportions; microhardness; wear resistance